Unraveling the dangers of mental health self-diagnosis: a study on the phenomenon of adolescent self-diagnosis in junior high schools - Nurismawan, Ach. Sudrajad; Lestary, Yunita Dinda; Purwoko, Budi; Alfaried, Hannes Zulfikar; Nafisah, Khilyatun (Universitas Islam Negeri Raden Intan Lampung, 2024)
Recently, self-diagnosis or diagnosing personal conditions without expert judgment (psychologists and psychiatrists) by matching one’s condition with information obtained from the internet (YouTube, TikTok, and websites) tended to be inaccurate and harmed adolescents with symptoms, especially among college students. However, it did not rule out the possibility of self-diagnosis related to mental health also being carried out by teenage students who were attending school. Using a qualitative phenomenological approach, this study focused 1) describes in detail the phenomenon of self-diagnosis in junior high school adolescents, 2) describe the causal factors and adverse impacts on junior high school adolescents when carrying out self-diagnosis and 3) explaining the implications and strategies for handling adolescent self-diagnosis for related parties (parents, homeroom teachers, counselors, and schools). This research also confirmed the researcher's initial suspicion that self-diagnosis could also occur among early adolescents and even 5th-grade elementary school students, not only among college students as in previous research in Indonesia. So that the phenomenon of adolescent self-diagnosis should not be underestimated, furthermore this finding needs to be followed up by related parties through synergy activities, mental health outreach with psychologists, and organizing parenting with parents.